PERBEDAAN MAKNA ALASAN PHK: IMPLIKASI HUKUM TERHADAP HAK-HAK PEKERJA DAN KEWAJIBAN PERUSAHAAN - Dewangga, Stevanus Andrian; Royhan Fakhri Megantara; Mardian Putra Frans (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Termination of Employment (PHK) or layoff is a significant action in the world of employment. Differences in the meaning of reasons for layoffs between workers and companies can be a source of complex conflict with significant legal enforcement. This research aims to analyze the differences in the meaning of reasons for layoffs between workers and companies as well as law enforcement regarding workers' rights and company obligations. The research method used is a descriptive analysis approach with reference to statutory regulations and court decisions regarding layoffs. Data was collected through literature studies, analysis of legal documents, and research of related cases in employment courts using a case approach. The research results show that differences in the meaning of reasons for layoffs between workers (Mr. ATNY) and companies (PT. Novell Pharmaceutical Laboratories) can be related to legal interpretation, factual assessment, or subjective perception. Workers may consider that the reasons for layoffs given by the company are invalid or unfair, while the company believes that these reasons are in accordance with applicable legal provisions. This difference in meaning can have a significant impact on workers' rights and company obligations. Therefore, efforts are needed to reach a common understanding regarding the legal interpretation of reasons for layoffs, so that it can help reduce conflict and increase fairness in layoffs.